Neurobehavioral alternations of the female offspring born to polycystic ovary syndrome model rats administered by Chinese herbal medicine - Xian Zhang; Lifang You; Xiaohui Zhang; Fangfang Wang; Yi Wang; Jue Zhou; Chang Liu; Fan Qu (BMC, 2021)
Abstract Background Chinese herbal medicine (CHM) has significant effects that improve the reproductive functions of patients with polycystic ovary syndrome (PCOS). However, the intergenerational effects of CHM on offspring and the underlying mechanism of CHM remain unclear. This study aimed to explore the effects and the underlying mechanism of CHM, specifically the Bu-Shen-Tian-Jing formula (BSTJF), on model rats with polycystic ovary syndrome (PCOS) and the neurobehavioral alterations of female offspring born to PCOS rats administered BSTJF. Methods High-performance liquid chromatography-mass spectrometry (HPLC-MS) and network pharmacology analysis were performed to identify the active ingredients and potential targets of BSTJF. Moreover, PCOS model rats were used to validate the role of BSTJF in reproduction and progeny neural development and to confirm the network pharmacological targets. Results A total of 91 constituents were characterized from BSTJF. The 20 most significant KEGG pathways and the high-frequency genes of these pathways were predicted to be putative targets of these molecules. The rat experiment showed that the downregulation of FOS protein expression in the ovarian granulosa cells of the PCOS group was reversed by BSTJF. The target residence time of the 5-week-old female offspring of the BSTJF group was higher than that of the PCOS group in the water maze experiment. Compared to the PCOS group, the changes in dendritic spine density, ultrastructure of neurons and synapses, and Gabrb1 and Grin2b protein expression levels in the hippocampus of female offspring were partially reversed in the BSTJF group. Conclusions BSTJF can effectively improve ovarian follicle development in PCOS rats and has positive effects on pubertal neurobehavioral alterations in the female offspring of these rats by reversing dendritic spine density, the ultrastructure of neurons and synapses, and the Gabrb1 and Grin2b protein expression levels in the hippocampus.